Pensees - Pascal, Blaise, 1623-1662 (Book collections on Project MUSE., 2022)
"The definitive English-language scholarly translation of the Pensees by Blaise Pascal (1623-1662), based upon the definitive French scholarly edition edited by Philippe Sellier. Also includes two shorter texts, the Exchange with M. de Sacy and The Life of Monsieur Pascal by Pascal's sister, Gilberte Perier. In addition to a preface and an introduction, there is a comprehensive apparatus criticus. The text was originally produced by a team of international Pascal scholars, who translated individual sections and was revised by the General Editor. The introduction situates the Sellier edition in the history of Pascal scholarship and highlights the advance its reordering of the fragments and of the folders or bundles represents, both the translation itself and the notes allow for a deeper reading of the text"--